Parenthood—Lost and Found: Exploring Parents’ Experiences of Receiving a Program in Emotion Focused Skills Training - Ansar, Nadia; Hjeltnes, Aslak; Stige, Signe Hjelen; Binder, Per-Einar; Stiegler, Jan Reidar (Frontiers in Psychology, 2021)
Background: Parents play a crucial part in the development, maintenance and deterioration of child difficulties (Gottman, 1998, Ginott, 1965). Emotion focused skills training for parents (EFST) targets parents’ capacity to provide their child with emotion-oriented skills to promote good child mental health (Dolhanthy & Lafrance, 2016). Few qualitative studies have specifically investigated parents’ experiences of receiving such programs. Aim: The purpose of the present study was to explore parents’ experiences of receiving EFST, and perceived changes in their everyday life and their understanding of their child’s difficulties following the program. Methods: Sixteen parents who completed a short-term EFST program (2 days group training and 6 hours of supervision) were invited to a qualitative study using in-depth interviews to explore how parents of children with externalizing and internalizing symptoms experienced this this program. A reflexive thematic analysis approach was used to analyze interview transcripts (Braun et.al, 2019; Binder et.al, 2012). Results: We identified three main themes: (1) Coming home in the role as a parent: a) A new way of being there with their child and b) The painful part – coming home to their own inner world, (2) Reclaiming parenthood in challenging situations: applying new tools and new learning, and (3) This is us – a new story about the family and its members. Conclusion: Parents described their inner life as changed and experienced having a wisdom and calmness inside them, which gave them higher self-confidence and self-acceptance. They were using the skills intuitively and creatively based on what was needed in challenging situations and described the family dynamic as changed. The findings also indicate that the therapists need to be aware of potential parental distress when working to change unpleasant emotions in such skill-based programs.